Integration of Realistic Mathematics Education (RME) and GeoGebra in Elementary School Geometry Learning: A Systematic Literature Review - Yuni Saraswati; Wiryanto Wiryanto; Rooselyna Ekawati (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
This systematic literature review explored the integration of Realistic Mathematics Education and GeoGebra in elementary geometry education, critically examining 27 empirical studies published between 2020 and 2025. This study examines the effectiveness of the integration in promoting conceptual understanding, engagement, motivation, and cognitive development in geometry education using the guidelines presented by PRISMA. This systematic literature review is conducted by carefully selecting studies from prominent databases such as Scopus, Web of Science, and Google Scholar. From the analysis, it is evident that the integration of RME and GeoGebra is effective in promoting learning outcomes, with approximately 80% of studies showing enhanced results in geometry understanding and student motivation. Some of the findings include the fact that GeoGebra, being a visual tool, enhances the contextual approach presented by RME, making it a very effective tool in creating an effective learning environment that connects concrete experiences with abstract mathematical concepts. From this study, it is also evident that there are gaps in the studies, with most studies being conducted in secondary education, while few are conducted in elementary education. Under methodological limitations, there is a lack of separation of the effects of GeoGebra and no longitudinal studies that focus on the long-term effects. The review offers recommendations on the way forward in terms of research direction, such as the design of RME and GeoGebra integrated modules and teacher training, as well as the exploration of the effects on student engagement and communication skills. The synthesis is beneficial in the understanding of how technology can change the face of realistic mathematics education in the teaching and learning of elementary geometry.